Latest Advances Towards Ras Inhibition: A Medicinal Chemistry Perspective. Issue 52 (22nd November 2016) - Sautier, Brice; Nising, Carl F.; Wortmann, Lars
Abstract: Owing to their high occurrence rate across many human cancers and their lack of druggability so far, mutant forms of the signaling protein Ras are currently among the most attractive (and elusive) oncology targets. This strong appeal explains the sustained effort in the field, and the ensuing progress has rekindled optimism regarding the discovery of Ras inhibitors. In this Minireview, we discuss the most recent advances towards irreversible inhibitors, and highlight approaches to inhibitors of Ras–effector interactions that have been overshadowed by the current focus on direct Ras inhibition. At the same time, we provide a critical assessment from a medicinal chemistry perspective. Abstract : Persistence pays off : After more than 40 years of effort, promising results are finally being reported the field of Ras inhibition. This Minireview presents the latest advances towards Ras inhibitors, as well as a critical assessment from a medicinal chemistry perspective. The picture shows the covalent inhibitor ARS‐853 in complex with K‐Ras G12C .